2020
DOI: 10.3390/ijgi9100593
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Relationship between Land Cover and Land Surface Temperature in Urban Areas: A Case Study in Geneva and Paris

Abstract: Currently, more than half of the world’s population lives in cities, which leads to major changes in land use and land surface temperature (LST). The associated urban heat island (UHI) effects have multiple impacts on energy consumption and human health. A better understanding of how different land covers affect LST is necessary for mitigating adverse impacts, and supporting urban planning and public health management. This study explores a distance-based, a grid-based and a point-based analysis to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(58 reference statements)
0
13
0
1
Order By: Relevance
“…Furthermore, WD and VD have much lower explanatory power for LST than MNDWI and NDVI [ 85 ]. It was demonstrated that the cooling effect of water bodies and vegetation is related to the density.…”
Section: Discussion and Prospectmentioning
confidence: 99%
“…Furthermore, WD and VD have much lower explanatory power for LST than MNDWI and NDVI [ 85 ]. It was demonstrated that the cooling effect of water bodies and vegetation is related to the density.…”
Section: Discussion and Prospectmentioning
confidence: 99%
“…Land cover composition is often quantified using remotely sensed spectral indices, including the Normalized Difference Vegetation Index (NDVI), the Normalized Difference Built-up Index (NDBI), and the Modified Normalized Difference Water Index (MNDWI). These indices are consistently and significantly correlated with LST across seasons [26][27][28]. Dense vegetation helps regulate LST, reducing LST in summer while increasing it in winter [20].…”
Section: Literature Reviewmentioning
confidence: 80%
“…These studies have sought to understand urban expansion, preserve green spaces, and mitigate the urban heat island effect. By mapping and analyzing impervious surfaces in Paris, researchers have contributed to urban planning efforts and the development of sustainable urban environments [20].…”
Section: Study Areamentioning
confidence: 99%